Insights into Imprinting: How Is the Phenomenon of Tribocorrosion at Head-Neck Taper Interfaces Related to Corrosion, Fretting, and Implant Design Parameters?. Issue 8 (5th August 2022) - Bormann, Therese; Müller, Ulrike; Gibmeier, Jens; Mai, Phuong Thao; Renkawitz, Tobias; Kretzer, Jan Philippe
Abstract: Background: Wear and corrosion at modular neck tapers in THA can lead to major clinical implications such as periprosthetic osteolysis, adverse local tissue reactions, or implant failure. The material degradation processes at the taper interface are complex and involve fretting corrosion, third-body abrasion, as well as electrochemical and crevice corrosion. One phenomenon in this context is imprinting of the head taper, where the initially smooth surface develops a topography that reflects the rougher neck taper profile. The formation mechanism of this specific phenomenon, and its relation to other observed damage features, is unclear. An analysis of retrieved implants may offer some insights into this process. Questions/purposes: (1) Is imprinting related to time in situ of the implants and to the taper damage modes of corrosion and fretting? (2) Are implant design parameters like neck taper profile, stem material, or head seating associated with the formation of imprinting? (3) Is imprinting created by an impression of the neck taper profile or can a different mechanistic explanation for imprinting be derived? Methods: Thirty-one THAs with cobalt-chromium-molybdenum-alloy (CoCrMo) heads retrieved between 2013 and 2019 at revision surgery from an institutional registry were investigated. Inclusion criteria were: 12/14 tapers, a head size of 36 mm or smaller, time in situ more than 1 year, and intact nonmodular stems without sleeve adaptors. After grouping the residual THAs according to stem type, stem material, and manufacturer, all groups of three or more were included. Of the resulting subset of 31 retrievals, nine THAs exhibited a still assembled head-neck taper connection. The median (range) time in situ was 5 years (1 to 23). Two stem materials (21 titanium-alloy and 10 stainless steel), three kinds of bearing couples (11 metal-on-metal, 13 metal-on-polyethylene, and seven dual-mobility heads), and two different neck taper profiles (six wavy profile and 25 fluted profile) were present in the collection. Four THAs exhibited signs of eccentric head seating. The 31 investigated THAs represented 21% of the retrieved THAs with a CoCrMo alloy head during the specified period. At the head tapers, the damage modes of corrosion, fretting, and imprinting were semiquantitatively rated on a scale between 0 (no corrosion/fretting/imprinting) and 3 (severe corrosion/fretting/imprinting). Corrosion and fretting were assessed applying the Goldberg score, with the modification that the scale started at 0 and not at 1. Imprinting was assessed with a custom scoring system. Rating was done individually at the proximal and distal head taper half and summed to one total damage score for each retrieval and damage mode. Correlations between the damage modes and time in situ and between the damage modes among each other, were assessed using the Spearman rank order correlation coefficient (ρ). Associations between imprinting and implant design parameters were investigated by comparing the total imprinting score distributions with the Mann-Whitney U-test. Metallographically prepared cross-sections of assembled head-neck taper connections were examined by optical microscopy and disassembled head and neck taper surfaces were assessed by scanning electron microscopy (SEM). Results: The imprinting damage score increased with time in-situ (ρ = 0.72; p < 0.001) and the corrosion damage score (ρ = 0.63; p < 0.001) but not with the fretting damage score (ρ = 0.35; p = 0.05). There was no difference in total imprinting score comparing neck taper profiles or stem materials, with the numbers available. Eccentric head seating had elevated total imprinting score (median 6 [interquartile range 0]) compared with centric seating (median 1 [2]; p = 0.001). Light optical investigations showed that imprinting can be present on the head taper surfaces even if the depth of abraded material exceeds the neck taper profile height. SEM investigations showed bands of pitting corrosion in the imprinted grooves. Conclusion: The microscopic investigations suggest that imprinting is not an independent phenomenon but a process that accompanies the continuous material degradation of the head taper surface because of circular damage on the passive layer induced by grooved neck tapers. Clinical Relevance: Material loss from head-neck taper connections involving CoCrMo alloy heads is a source of metal ions and could potentially be reduced if hip stems with smooth neck tapers were used. Surgeons should pay attention to the exact centric seating of the femoral head onto the stem taper during joining of the parts.